State-amplified platform inequality: The economic geography of digital cultural policy in China - Li-De Su; Zhi-Hui Pang; Ze-Hao Tan; Zhi-Xiang Wen; Mei Ren; Yang Zhang (PLoS ONE, 2026)
Digital platformization is reshaping not only markets but also the spatial organization of cultural development. While platform concentration has been widely examined in commercial sectors, its territorial consequences within national cultural industries remain underexplored. This study investigates whether China’s 2017 digital cultural policy was associated with widening regional divergence in the cultural economy. We frame this process as state-amplified platform inequality, in which state-led digital policy interacts with platform-based accumulation dynamics to reinforce the advantages of already dominant regions. Using national- and provincial-level data from 2012 to 2023, we combine interrupted time series regression, Bai–Perron structural break tests, and inequality analysis of the radio and television broadcasting sector. The results show that post-2017 growth momentum weakened at the national level and that provincial trajectories became increasingly uneven, with most regions exhibiting negative post-policy slopes. In broadcasting, regional concentration intensified sharply: the Gini coefficient rose from 0.442 to 0.841, the spatial Gini index from 0.352 to 0.689, and the Theil index from 0.439 to 1.839. Structural break tests further identify 2017 as a common breakpoint across key concentration measures. These findings suggest that state-led digital modernization may deepen rather than reduce territorial inequality when implemented in platformized sectors characterized by cumulative advantage. The study contributes a theory-informed account of the economic-geographic and distributive consequences of digital cultural policy and highlights the need to evaluate digital development not only by aggregate growth, but also by its spatial distribution.